The right heart: acute and chronic issues - Churchill, T. W.; Baggish, A. L. (Current Treatment Options in Cardiovascular Medicine, 2017)
Cardiovascular remodeling in response to sustained moderate and high-intensity exercise is a well-established phenomenon. Following more than a century of work focused on the left ventricle (LV), remodeling of the right side of the heart has recently become a topic of considerable scientific and clinical interest. Morphologic and functional changes have now been well documented in the right ventricle (RV) after isolated bouts of endurance exercise and in association with long-term sustained training. Although exercise-induced cardiac remodeling is classically viewed as an adaptive, clinically benign process, it has recently been hypothesized that repetitive bouts of intense exercise may trigger pathologic changes in the RV characterized by patchy fibrosis and a predisposition to arrhythmia. At present, this concept remains speculative due to the absence of definitive clinical data. While we await scientific clarification of this intriguing hypothesis, several practical clinical considerations are noteworthy. RV dilation is common among trained endurance athletes. As such, asymptomatic athletes with RV dilation do not require additional diagnostic evaluation unless dilation is accompanied by substantial decrements in systolic function or other structural abnormalities suggestive of genetic heart disease. In contrast, RV dilation among athletes with either symptoms or a family history of genetic heart disease requires extensive multi-modality assessment including maximal effort-limited exercise testing, ambulatory rhythm monitoring, advanced non-invasive imaging, and invasive electrophysiology study. This review will discuss the contemporary understanding of how the RV responds to exercise with an emphasis on the relevance of this phenomenon in clinical cardiovascular practice.